PROBLEMATIKA PERLINDUNGAN TENAGA KERJA INDONESIA DI LUAR NEGERI - Jaingin Tambunan (JURNAL MITRA MANAJEMEN, 2014)
ABSTRACTState law is a picture of the kind of country that is considered by a nation and once aspired to be realizedin reality. Our country is a country that is based on the 1945 constitution. Judging from the 1945perspectif Human Right, constitutional rights of citizens and everyone in the work provided for in Article27 Paragraph (2) and Article 28 Paragraph (2). Conection with the protection ofhuman right in the work,especially against Indonesian Worker who work abroad are often used as the object of human trafficking.Indonesian labour is every Indonesian citizen qualified to work abroad for a certain period of time andreceive a reward. Each of the Indonesian labour come in destination country for work, shall report to theRepresentative of the Republic of Indonesia in the destination country. After delivery or placement ofIndonesian workers who work abroad is certainly a certain time will be returned to his residence in thecountry. The settings in the placement and protection of fereign workers in order to protect overseasworkers.Keyword: Problems of Indonesian Labor.